Factors influencing choice of residency program among medical intern doctors and medical students: a cross-sectional survey - Ali Al Ajmi; Masoud Kashoub; Ibrahim S. Al-Busaidi; Mohammed Al Rashdi; Moza AlHussaini; Arwa Alsaidi; Mohammed Al Rawahi; Abdullah M. Al Alawi (BMC Medical Education)
Abstract Introduction The global shortage of healthcare professionals is a critical concern, with an estimated deficit of 18 million workers by 2030, particularly in low- and middle-income countries. Oman faces challenges with its doctor-to-population ratio falling below the global average. This study examines the factors influencing residency program choices among Omani medical students and interns, with a specific focus on internal medicine. Methods A cross-sectional survey using a validated, context-specific questionnaire was distributed to medical interns and clinical clerkship students at Sultan Qaboos University and the National University.Descriptive statistics and univariate analyses were used to explore demographic patterns and factors influencing specialty choices, including internal medicine. Results Out of 803 distributed surveys, 459 responses were collected, yielding a response rate of 58.8%. The study comprised 459 participants, with 26.1% males and 73.9% females, and an average age of 23.85 years (SD = 1.70). Internal medicine was selected by 19.9% of participants. Key factors influencing the choice of internal medicine included societal respect and a comfortable specialty department atmosphere. Gender differences showed that men prioritized factors such as aptitude for the specialty, attainable lifestyle, and risk of malpractice lawsuits, while women focused on the workplace environment. Role models played an important role in career decisions, with 25.7% of participants identifying a physician role model. Conclusion Internal medicine emerged as a popular specialty among Omani medical students and interns, driven by intellectual stimulation, job security, and work-life balance. Addressing gender-specific influences and expanding mentorship opportunities are essential to optimizing career guidance. The findings also emphasize the need for targeted strategies to address rural healthcare professional shortages. Clinical trial number Not applicable.